Wound care made incredibly visual (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"'Wound Care Made Incredibly Visual,' Second Edition, is an innovative reference that combines detailed photographs and graphics with concise, informative text to make the complex concepts of wound care easy to understand. Thoroughly updated with the latest clinical practice guidelines and documentation, this new approach to clinical content maximizes the power of visual thinking by "showing" as well as "telling" about the latest wound care information techniques. The highly visual nature of this book makes the fundamentals and advancements in the treatment of wound care clear and understandable, enabling quick review and comprehension for practical application."--Provided by publisher.